Reduced Model and Comparative Analysis of the Thermal Performance of Indirect Solar Dryer with and without PCM - Camilo Ramirez; Mario Palacio; Mauricio Carmona (Energies, 2020)
A thermal model is proposed to analyze the performance of an indirect solar dryer (ISD) with latent heat storage using phase change material (PCM). The estimations are compared with experimental data presented in the scientific literature taken in real conditions. The validated thermal model is used in order to address a comprehensive analysis of the performance of the ISDs under the same operation conditions, the model is able to estimate the temperatures of glass cover, absorber plate, PCM, useful heat, thermal and storage efficiencies, and variables that are difficult to measure experimentally such as liquid fraction, heat losses, and accumulated energy of the ISDs. Three study cases are considered: Case 1 consists of two collectors with and without alternating nocturnal and diurnal operation (benchmarking case). Case 2 and 3 consist in a unique collector operating continuously for 24 h with PCM and without PCM, respectively. It was determined that the use of PCM in ISD increased the night thermal performance and extended the operational time of the system. On the other hand, results indicate that the use of two alternating collectors presents similar discharge behavior to using one collector with PCM operating continuously. Concerning the overall thermal performance, cases 1, 2, and 3 obtained thermal efficiencies of 20%, 28%, and 24%, respectively.